Police Community Support Officers - O'Neill, Megan, 1974- (Oxford : Oxford University Press, 2019)
An analysis of findings from a comprehensive observational study of police community support officers (PCSOs), examining the distinct culture of PCSOs, what relationships between PCSOs and police officers are like within a rapidly diversifying organisation and how this develops the policing pluralisation discourse.
Previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on May 10, 2019).
Keywords: Community policing -- Great Britain